3x-7=6+4x

Simple and best practice solution for 3x-7=6+4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-7=6+4x equation:


Simplifying
3x + -7 = 6 + 4x

Reorder the terms:
-7 + 3x = 6 + 4x

Solving
-7 + 3x = 6 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-7 + 3x + -4x = 6 + 4x + -4x

Combine like terms: 3x + -4x = -1x
-7 + -1x = 6 + 4x + -4x

Combine like terms: 4x + -4x = 0
-7 + -1x = 6 + 0
-7 + -1x = 6

Add '7' to each side of the equation.
-7 + 7 + -1x = 6 + 7

Combine like terms: -7 + 7 = 0
0 + -1x = 6 + 7
-1x = 6 + 7

Combine like terms: 6 + 7 = 13
-1x = 13

Divide each side by '-1'.
x = -13

Simplifying
x = -13

See similar equations:

| 2r+5+2r+4r-3+r=65 | | lx-4l=-15 | | t=4s+4.95 | | -5-4=9 | | -8=-(7n+1) | | (5x+3)(6x-8)= | | x^2-16x-4=0 | | 9x^2-1.4x+0.6=0 | | -13-4=9 | | (10x-6)(5x+4)= | | 9x^2-1.4+0.6=0 | | 5x*x-8x=0 | | -9x^0=0 | | 12a+7=7a+2 | | 3(5x-3)-10=-34 | | 49=26-8(3-5w) | | 8.833x^2-1.422x+0.5842=0 | | (2a+7)(4a+10)= | | 10x-5-4x-3+2=0 | | -6=3(3x-5) | | 7x+4=45 | | -12=2(5x-1) | | 21x+15=15 | | -w-2=42 | | 0=x^2+6x-8 | | 6a+2=-a+30 | | (xy)(x^2y)(x^2y)(x^2y)(x^2y)=0 | | 1x+4y=168 | | 21x+5=15 | | x^2-4x-37=0 | | 3x^2+9x-2=-4 | | (xy)(x^2y)(xy)(x^2y)(xy)(x^2y)(xy)(x^2y)=0 |

Equations solver categories